Electrically driven assembly of CdTe quantum dots into photoconductive microwires1. Issue 8 (28th February 2015) - Maheshwari, Gaurav; Mittal, Mona; Sapra, Sameer; Gupta, Shalini
<x xml:space="preserve">Abstract</x> Low energy, low cost quantum dot nanocrystal assembly into one-dimensional microwires for optoelectronic device applications.